PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, DISIPLIN KERJA, DAN KOMUNIKASI INTERPERSONAL TERHADAP KUALITAS LAYANAN GURU DI SMK GUGUS 02 KOTA TANGERANG SELATAN - Rohani Siregar; Siti Zubaidah; Rian Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of situational leadership style, work discipline, and interpersonal communication on the quality of teachers' services at the Vocational High Schools (SMK) Cluster 02 in South Tangerang City. The study employed a quantitative approach using a survey method. The research population consisted of 167 teachers, with a sample of 118 respondents determined using the Slovin formula. Data were collected through a Likert-scale questionnaire that had met the validity and reliability requirements. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS software. The results revealed that situational leadership style had a positive and significant effect on the quality of teachers' services, with a regression coefficient (β) of 0.345 and a t-value of 20.970, which exceeded the t-table value of 1.981. Work discipline also had a positive and significant effect on the quality of teachers' services, with a regression coefficient (β) of 0.296 and a t-value of 16.453, which exceeded the t-table value of 1.981. Furthermore, interpersonal communication had a positive and significant effect on the quality of teachers' services, with a regression coefficient (β) of 0.317 and a t-value of 16.973, which exceeded the t-table value of 1.981. Simultaneously, situational leadership style, work discipline, and interpersonal communication had a positive and significant effect on the quality of teachers' services, as indicated by an F-value of 373.447, which was greater than the F-table value of 2.684, with a significance level of 0.000 (< 0.05). The coefficient of determination (R²) of 0.908 indicates that 90.8% of the variance in the quality of teachers' services can be explained by the three independent variables, while the remaining 9.2% is influenced by other factors outside the research model. Among the independent variables, situational leadership style was found to have the strongest influence on the quality of teachers' services.